Min Mūjibāt al-Tawhīd Tark mā Yunāfīh - Hasan Basri Salim (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2003)
The main and the first thing that must be done by religious people is to bring together between belief and disbelief in his heart. That is, when he believed in Allah swt., He should disbelieve besides Him. When he believes in socialism, he should disbelieve liberalism. 23 years of great struggle of the Prophet Muhammad., 13 of those years at Mecca al-Mukarromah voiced union between faith in Allah, and disbelief to idols.